This is social commerce : turning social media into sales - Clapperton, Guy. (Chichester : Capstone, 2012)
'Step-by-step guide to setting up your own commerce site within social media platforms such as Facebook. Building a loyal community who will keep coming back and buying from you. How to offer superb customer service to your social media consumers. Developing new product especially for this new environment. Measuring your ROI'--
Includes index.
Keywords: Electronic commerce -- Social aspects; Internet marketing -- Social aspects; Customer clubs; Cooperative societies; consumer cooperatives; Online social networks; Social media